Analysis of the Influence of Workload, Physical Environment, and Work Motivation on the Performance of Field Employees of the Regional Public Drinking Water Company (Perumdam) Tirta Yapono, Ambon City - Purimahua, Melian; Leiwaherilla, Novalien Carolin; Pentury, Gerrit M. (Jurnal Ekonomi, 2024)
This study examines the effect of workload, compensation and motivation on work performance on the performance of field employees of the Tirta Yapono Regional Drinking Water Company (PERUMDAM) in Ambon City. This study is an explanatory research type. Explanatory research is a study whose data analysis is to determine the relationship between variables and other variables. Based on the results of the study, it shows that workload (X1) has a t-value of 0.527 and a significant value of 0.601. This shows that sig. 0.601> 0.05, which means that the hypothesis is rejected, so there is no effect of workload on performance. The work environment variable (X2) has a t-value of 2,240 and a significant value of 0.030 <0.05, which means that the hypothesis is accepted, so that the work environment affects performance. The work motivation variable (X3) has a t-value of 2,228 and a significant value of 0.031 <0.05, which means that the hypothesis is accepted, so that work motivation affects performance.Based on the F test results table with a significance value of 0.001, which is smaller than 0.05 (0.000 <0.05). From these results, the independent variables, namely workload, work environment, and work motivation, have a significant positive effect on the dependent variable, namely performance.